Culture of Building Environmental Awareness in Orphanages: Strategy and Implementation of Nature Conservation Programs: - - Riyanto Adji; Septi Ariwibowo; Dewi Ratnasari (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Large cities' extremely high levels of activity contribute to rising air pollution, which can make residents feel stressed. We must be able to find a solution to this issue, but we cannot deny or resist this circumstance. Environmental pollution from garbage and air pollution is a common issue in large cities like Bekasi City, one of the supporting cities for DKI Jakarta province. For the city of Bekasi to have alternative options for environmental sustainability, these two issues need to be addressed. Teaching people about the value of preserving the environment is one of the practical steps being taken to maintain and preserve it in the Bekasi City area. Since it can create a culture of understanding of the value of protecting the environment, this education must be continued for upcoming generations. The goal of choosing education at the orphanage was to encourage children's involvement in caring for the conditions of the surrounding environment in urban areas. Researchers and a team implemented this education at one of the homes in Bekasi City. Sorting and choosing rubbish is one of the actual tasks completed in order to prevent waste accumulation. As a tangible step toward supplying oxygen in the future, planting trees is another activity. The outcomes of carrying out this activity can be successful, and it is hoped that it will foster a positive culture within the community by emphasizing the value of sustaining a sustainable environment in the vicinity of their homes.